Transformation of supercapacitive charge storage behaviour in a multi elemental spinel CuMn2O4 nanofibers with alkaline and neutral electrolytes - Kunwar, Ria; Krishnan, Syam G.; Izan Izwan, Misnon; Zabihi, Fatemeh; Yang, Shengyuan; Yang, Chun-Chen; Rajan, Jose (Springer, 2021)
Electrode material has been cited as one of the most important determining factors in classifying an energy storage system’s charge storage mechanism, i.e., as battery-type or supercapacitive-type. In this paper, we show that along with the electrode material, the electrolyte also plays a role in determining the charge storage behaviour of the system. For the purpose of our research, we chose multi-elemental spinal type CuMn2O4 metal oxide nanofibers to prove the hypothesis. The material is synthesized as nanofibers of diameter ~ 120 to 150 nm in large scales by a pilot scale electrospinning set up. It was then tested in three different electrolytes (1 M KOH, 1 M Na2SO4 and 1 M Li2SO4), two of which are neutral and the third is alkaline (KOH). The cyclic voltammograms and the galvanostatic charge–discharge of the electrode material in a three-electrode system measurement showed that it exhibit different charge storage mechanism in different electrolyte solutions. For the neutral electrolytes, a capacitive behaviour was observed whereas a battery-type behaviour was seen for the alkaline electrolyte. This leads us to conclude that the charge storage mechanism, along with the active material, also depends on the electrolyte used.